Origin and adaptive evolutionary trajectory of the 3′ UTR–derived sRNA UhpU in Enterobacteriaceae - Xiaomin Chen; Cheng Bei; Jialei Liang; Yaomei Yang; Yuanyuan Ruan; Qian Gao; Chuan Wang (Proceedings of the National Academy of Sciences, 2025)
Bacterial small RNAs (sRNAs) derived from mRNA 3′ untranslated regions (3′ UTRs) have emerged as important regulators of gene expression, yet their evolutionary origins and functional diversification remain poorly understood compared to the protein-coding sequences of the same transcripts. In this study, we present a comparative analysis of the biogenesis and regulatory functions of UhpU, a 3′ UTR–derived sRNA from the hexose phosphate transporter gene uhpT , in Escherichia and Salmonella . We show that UhpU likely originated as a processed sRNA generated by RNase E cleavage in Enterobacteriaceae, enabling repression of genes in the hexose phosphotransferase system, thereby contributing to hexose phosphate homeostasis in coordination with its parental gene. In Escherichia , UhpU subsequently evolved the ability to repress mprA , a transcriptional repressor, via a UhpU-binding site introduced by a horizontally acquired DNA fragment that extended the mprA 5′ UTR. After divergence from the most recent common ancestor with Escherichia albertii , the lineage comprising Escherichia coli , Escherichia fergusonii , and Shigella acquired a FliA-dependent promoter within the uhpT coding region, allowing independent transcription of UhpU and establishing it as a dual-biogenesis sRNA. Together, our results outline a stepwise trajectory in which UhpU evolved from a processing-derived metabolic regulator to an sRNA with expanded regulatory connections and a lineage-specific FliA-dependent transcriptional program in Escherichia .